ANALISIS HAMBATAN PELAKSANAAN PRAKTIKUM IPA TERPADU DI DUA SMP NEGERI KOTA JAMBI - Marcella, Zheka; Susanti, Nova; Dani, Rahma (EduFisika: Jurnal Pendidikan Fisika, 2018)
This study aims to find out the obstacles in the implementation of the integrated science practicum faced by teachers and students in the 17 State Junior High Schools in Jambi City and 19 Public Schools in Jambi City. This type of research uses a mixed methods approach. The population of this study were integrated science teachers and eighth grade students of 17 Kota Jambi Middle School and Jambi City 19 Middle School with a sample of 133 students and two integrated science teachers. Data collection instruments used student questionnaires and teacher interviews. Data were analyzed statistically descriptive for quantitative data and miles and huberman models for qualitative data. The results showed practicum implementation was 64% with good category in Jambi City 17 Middle School and 66% with good category in Jambi City 19 Middle School, so that the results of the students did not experience obstacles in the implementation of school practicum.